2021
DOI: 10.3390/agronomy11071385
|View full text |Cite
|
Sign up to set email alerts
|

Nepheline Syenite and Phonolite as Alternative Potassium Sources for Maize

Abstract: Some silicate rocks are a rich source of potassium (K), with the possibility for use in agriculture. The present study aimed to evaluate the agronomic efficiency index (AEI) of nepheline syenite (NS) and phonolite (PN) rocks in comparison with potassium chloride (KCl) as a K source in maize production. An experiment was conducted in a greenhouse in Ilha Solteira, São Paulo, Brazil. A maize hybrid was grown in 8 L pots filled with 6 kg of soil with a low K concentration and contrasting physical attributes (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Several technologies might be employed to boost K-release in K-bearing agrominerals. These include ultra ne grinding that increase the proportion of particles < 0.074 mm, which increased the K-release of a phonolite from Minas Gerais, Brazil (Nogueira et al 2021), hydrothermal treatment with sulfuric acid (Safatle et al 2020), incubation of waste mica with organic acids and K-solubilizing microorganisms (Basak 2019), co-composting (Basak 2018), among others (Pramanik et al 2019(Pramanik et al , 2020. It is important to use materials that promote agronomic e ciency and keep the transport distances short, these technologies have potentials as local solutions for the use of K-rich agrominerals to cultivate annual crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several technologies might be employed to boost K-release in K-bearing agrominerals. These include ultra ne grinding that increase the proportion of particles < 0.074 mm, which increased the K-release of a phonolite from Minas Gerais, Brazil (Nogueira et al 2021), hydrothermal treatment with sulfuric acid (Safatle et al 2020), incubation of waste mica with organic acids and K-solubilizing microorganisms (Basak 2019), co-composting (Basak 2018), among others (Pramanik et al 2019(Pramanik et al , 2020. It is important to use materials that promote agronomic e ciency and keep the transport distances short, these technologies have potentials as local solutions for the use of K-rich agrominerals to cultivate annual crops.…”
Section: Discussionmentioning
confidence: 99%
“…Silicate rocks containing K-bearing minerals and K-rich rocks such as phonolite and nepheline syenite (Nogueira et al 2021;Soratto et al 2021), glauconite bearing rocks (Safatle et al 2020), biotite (Basak 2018(Basak , 2019Pramanik et al 2018Pramanik et al , 2019 are available in a regional scale, and various studies have shown the successfully use of selected rocks in agriculture. Despite this, these nutrient sources cannot provide all plant needing's, requiring the combination with other fonts.…”
Section: Introductionmentioning
confidence: 99%
“…The organic matter (OM) and macronutrient contents of the soil and leaves were evaluated as described by Nogueira et al (2021). Homogeneous composite samples were collected from three points between cultivation rows in the 0-20 cm layer to measure the OM and macronutrient concentrations in the soil.…”
Section: Chemical Characterization Of Soil and Plantmentioning
confidence: 99%
“…The use of rocks as fertilizers arises as an option to reduce the dependence on potassium fertilizers, and the slow-release fertilizer being directly applied directly to the soil or in the production of K salts (Silva et al, 2012;Santos et al, 2016). However, there are challenges related to the use of rocks as potassium fertilizers, such as low solubility or even low K 2 O content compared to KCl, as well as the supply of nutrients in the right amounts and at the right time for each crop (Boldrin et al, 2019;Nogueira et al, 2021).…”
Section: _______________________________________________mentioning
confidence: 99%